KAJIAN TAFSIR SURAT AL-'ALAQ AYAT 1-5 DALAM KITAB AL MUNIR DENGAN METODE TAFSIR KONVENSIONAL DAN KONTEKSTUALISASINYA PADA ZAMAN SEKARANG - Putri Maria Ulvah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
The interpretation of the Qur'an is knowledge to understand and study more in the verses contained in the Qur'an in order to explain the meaning of the Qur'anic content, especially verses that are still vague or incomprehensible. One of the letters in the Qur'an which is sometimes still difficult to understand its meaning is the letter al–Alaq verse 1-5. Surat al-laAlaq is simply the command to read. It is felt that it is still very common for ordinary people to interpret this meaning. Therefore, the letter al-laAlaq verse 1-5 needs to be studied in greater depth and broadly using conventional interpretations. Conventional Interpretation is one of the classical methods of interpretation and is still focused on the textuality of a verse of al-Qur'an and the book of Al Munir is a book of interpretation that is patterned on the conventional interpretation method. Keywords: Letter al'Alaq 1-5, Kitab al Munir, Conventional Interpretation